Electricity Supply in Khartoum: the planned, the delivered, the experienced - Hassan, Basheir Hassan Razaz (Department of Environmental and Geographical Science, 2022)
As the first step in rethinking infrastructure configurations and their alternatives, this thesis aims at looking into the existing policy framework that governs electricity supply in Khartoum, its implementation and how it's experienced by Khartoum's residents. By zooming into one locality in Khartoum, the “Eastern Nile Locality”, the research has attempted to analyse the ways with which the limited electricity infrastructure is planned and allocated through its translation into policy frameworks in neighbouring areas falling under different zoning classification that correspond to their residents' income brackets. Review of the policy framework was conducted firstly, using a mix of desktop research and interviews with officials from the relevant institutions, investigating the key guidelines that govern electricity distribution across the various residential zones in terms of no/access to the grid, tariff regimes, contractual arrangements, alternative configurations and so on. The second part of the research was using ethnographic research methodologies to examine users' experience of electricity supply in its material and non-material dimensions. The studied cases revealed three main user categories; firstly, those grid-connected via the standard producers set by the Electricity Distribution Company. The second are those gridconnected via emerging models that could be classified as micro-financed co-production gridconnection. The third are those who remain off-grid and follow alternative routes. These varying regimes of service delivery are experienced by Khartoum residents on multiple levels, the most significant of which are firstly linked to users' experience of electricity as an unrivalled energy form that could be converted into a multiplicity of other forms, or its functional dimension as a modern technology that dis/enables greater space-time manipulation. Secondly, its more symbolic or representational aspects and their translation into social codes that define modern citizens and modernized states. Lastly, users' experience has pointed to the close link that the users make between electricity and the different relations that they form in their endeavors to access power services as in the different set of financial, legal, institutional and social relations and their implications in shaping subjectivities and articulating political positions.